2021
DOI: 10.1080/1828051x.2021.1893134
|View full text |Cite
|
Sign up to set email alerts
|

Comparing three textural measurements of chicken breast fillets affected by severe wooden breast and spaghetti meat

Abstract: Comparing three textural measurements of chicken breast fillets affected by severe wooden breast and spaghetti meat Ant on Pascual Guzm an a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…The relative abundance of the extra-myofibrillar water and the mobility of intra-myofibrillar water affect drip losses of WB meat, while the mobility of intra-myofibrillar water is crucial for cooking losses (Pang et al, 2020). Indeed, compared to normal meat, higher dripping and cooking losses have been reported also in SM meat (Soglia et al, 2016;Baldi et al, 2018;Pascual et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The relative abundance of the extra-myofibrillar water and the mobility of intra-myofibrillar water affect drip losses of WB meat, while the mobility of intra-myofibrillar water is crucial for cooking losses (Pang et al, 2020). Indeed, compared to normal meat, higher dripping and cooking losses have been reported also in SM meat (Soglia et al, 2016;Baldi et al, 2018;Pascual et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…As for texture and tenderness, among the most important indicators of meat quality (Warner et al, 2022), results about changes due to myopathies are often inconsistent among studies, also as a consequence of differences in meat status (fresh vs frozen), cooking process (raw vs cooked), severity degree of myopathies, sampled cuts, textural methods and, within the same method, measurement conditions (Soglia et al, 2017;Baldi et al, 2019;Pascual et al, 2021). For example, at low compression rates, the resistance is mainly due to the myofiber since the connective tissue has the property of expanding due to its elasticity without interfering with the muscle resistance, whereas at higher compression rates the connective tissue is an important part in the resistance of the muscle (Campo et al, 2000;Campo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the occurrence of SM is associated with higher meat yellowness and ultimate pH values (Baldi et al, 2018;Soglia et al, 2019a;Tasoniero et al, 2020). While Yu et al (2020) did not find any difference in water holding capacity assessed on fresh, frozen, and cooked SM samples, Pascual et al (2021) reported greater drip and cooking losses in SM samples compared to normal ones. The latter result corroborates the outcomes obtained through time-domain nuclear magnetic resonance analysis, which evidenced increased amounts of bound and extra-myofibrillar water fractions in SM fillets (Soglia et al, 2019a).…”
Section: Implications On Meat Quality and Practical Solutionsmentioning
confidence: 84%
“…As concern texture, compression forces obtained for raw meat did not evidence any difference between SM samples and their unaffected counterparts (Baldi et al, 2019). However, after the cooking process, SM fillets showed a softer texture following compression, Meullenet-Owens Razor Shear as well as Allo-Kramer tests (Baldi et al, 2019;Pascual et al, 2021), probably as a result of their reduced collagen cross-linking degree. In addition, a number of studies have been carried out to investigate whether SM lesions display intra-fillet variations, revealing that the occurrence of this condition mainly alters meat composition and quality traits of the superficial layer of the muscle, while the deep one is almost unaffected (Baldi et al, 2019;Tasoniero et al, 2020;Yu et al, 2020).…”
Section: Implications On Meat Quality and Practical Solutionsmentioning
confidence: 85%
See 1 more Smart Citation